2007
DOI: 10.1016/j.jpeds.2006.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Children and Adolescents with Neurofibromatosis Type 1

Abstract: Objective-To assess if children and adolescents with neurofibromatosis type 1 (NF1) have decreased bone mineral density (BMD).Study design-Bone densitometry of the whole body, hip and lumbar spine was utilized in a case:control design (84 individuals with NF1: 293 healthy individuals without NF1). Subjects were 5-18 years of age. Individuals with NF1 were compared to controls using an analysis-of-covariance with a fixed set of covariates (age, weight, height, Tanner stage, and sex).Results-Individuals with NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 33 publications
9
84
3
1
Order By: Relevance
“…Decreased BMD in both sexes at an early age has been reported in up to 50% of individuals with NF1 [Illes et al, 2001;Kuorilehto et al, 2004b;Lammert et al, 2005;Dulai et al, 2007;Stevenson et al, 2007;Yilmaz et al, 2007;Brunetti-Pierri et al, 2008;Duman et al, 2008]. This may be related to an inadequate increase in bone remodeling observed by both bone histomorphometry and changes in circulating bone markers [Stevenson et al, 2008;Seitz et al, 2009].…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased BMD in both sexes at an early age has been reported in up to 50% of individuals with NF1 [Illes et al, 2001;Kuorilehto et al, 2004b;Lammert et al, 2005;Dulai et al, 2007;Stevenson et al, 2007;Yilmaz et al, 2007;Brunetti-Pierri et al, 2008;Duman et al, 2008]. This may be related to an inadequate increase in bone remodeling observed by both bone histomorphometry and changes in circulating bone markers [Stevenson et al, 2008;Seitz et al, 2009].…”
Section: Osteoporosismentioning
confidence: 99%
“…The anterolateral bowing seen in patients with NF1 is distinct from the bilateral physiological bowing common in children as they begin to walk. Radiographically, tibial bowing in NFL patients prior to fracture usually appears as cortical thickening and medullary canal narrowing at the apex of the convexity, typically near the junction of the middle and distal thirds of the tibia [Stevenson et al, 2007] (Fig. 2).…”
Section: Dysplasia Of the Tibia And Other Long Bonesmentioning
confidence: 99%
“…Several studies have reported decreased bone mineral density in NF1 individuals (11)(12)(13)(14)(15)(16), thus pointing to an underlying disorder of skeletal homeostasis and mineralization in humans with NF1. One of these studies reported that all postmenopausal NF1 women in the cohort had either osteoporosis or osteopenia (13).…”
mentioning
confidence: 99%
“…There is increasing evidence from animal models and human data that the heterozygous NF1 state can cause generalized bone abnormalities such as osteopenia [Kuorilehto et al, 2004;Lammert et al, 2005;Stevenson et al, 2007;Brunetti-Pierri et al, 2008]. Other skeletal complications occur with a great deal of variability of expression; some such as tibial dysplasia/pseudarthrosis occur very rarely, with an incidence of only 3-5% of NF1 patients.…”
Section: Discussionmentioning
confidence: 99%